2020
DOI: 10.1177/2192568220960753
|View full text |Cite
|
Sign up to set email alerts
|

Supine Imaging Is a Superior Predictor of Long-Term Alignment Following Adult Spinal Deformity Surgery

Abstract: Study Design: Retrospective cohort study. Objective: To investigate correlations between preoperative supine imaging and postoperative alignment. Methods: A retrospective review was conducted of a single-institution database of patients with adult spinal deformity (ASD). Patients were stratified by fusion location in the lumbar or thoracic spine. Outcomes of interest were postoperative lumbar lordosis (LL) and thoracic kyphosis (TK). Sagittal alignment parameters were compared and correlation analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the mean L1S, LL, and SS values reported for this group were very close to that of healthy subjects and can be accepted as an asymptomatic group. On the other hand, we thought that evaluation of spinopelvic parameters in supine position strengthened our study, because the importance of supine imaging tools has been increasing for several reasons [26][27][28]. First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, the mean L1S, LL, and SS values reported for this group were very close to that of healthy subjects and can be accepted as an asymptomatic group. On the other hand, we thought that evaluation of spinopelvic parameters in supine position strengthened our study, because the importance of supine imaging tools has been increasing for several reasons [26][27][28]. First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [26].…”
Section: Discussionmentioning
confidence: 65%
“…First, the correlation between the spinopelvic parameters are strongest in the supine position and lumbosacral sagittal alingment in the supine position is appromixately equal to that in the prone position which is actually intraoperative position, so supine images can be helpful for the surgical planing [ 26 ]. Second, the difference between LL values measured in supine and standing position was found correlated with postoperative outcome in the patients with adult spinal deformity [ 27 , 28 ]. We believe that supine imaging will be utilized more commonly in the future for the diagnosis and the treatment of spinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cheung et al reported that there was a significant difference between the fulcrum bending Cobb (28°) and postoperative Cobb angles at 1 month (15°) and 2 years after surgery (16°) [ 13 ]. Elysee et al investigated the correlation between preoperative supine imaging and postoperative alignment in adult spinal deformity (ASD) rather than AIS and reported that the difference between the supine and preoperative Cobb angles was 15.1° [ 27 ]. In our study, the mean difference between the supine and postoperative Cobb angles was 21.2° for the thoracic curve and 21.8° for the lumbar curve.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Karikari et al 9 note that “stiff lumbar spines,” or those that have a <33% change in LL between the supine and standing position, are more likely to require a three-column osteotomy to achieve satisfactory deformity correction. Elysee et al 20 in their retrospective analysis of 99 patients with severe sagittal deformity determined that supine LL and pelvic incidence were the only significant predictors of post-operative LL. The authors also found that standing pre-operative lumbar lordosis poorly correlated with post-operative result.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we have found that supine imaging correlates with intraoperative decision-making as it is more reflective of prone positioning 19 and is superior to standing imaging in the prediction of long-term post-operative lumbar lordosis and thoracic kyphosis. 20 We hypothesized that understanding regional lumbar flexibility by comparing standing and supine radiographs can help identify regions of the lumbar spine that most significantly contribute to PI–LL mismatch. Such knowledge can dictate the need for, extended proximal fusion constructs in order to avoid proximal residual deformity and adjacent segment disease (ASD).…”
Section: Introductionmentioning
confidence: 99%